การสร้างแบบฝึกเพื่อพัฒนาทักษะอ่านจับใจความของนักเรียนชั้นประถมศึกษาปีที่ 2 - ทามนตรี, ประภาวดี (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract The purpose of this research was to develop practical packages to improve the reading skills of primary school grade-2 students to meet a standard criterion of 80/80, and develop a standard comparison for achievement before and after use. The sample consisted of 35 students from Chulalongkorn University Demonstration School chosen by the random group method from seven classrooms. The experiment was set up for eight weeks and the data was analyzed by utilizing the average, percentage, standard deviation and T-test. It was revealed that the practice improved the reading skills of primary school grade-2 students who had an efficiency score equal to 86.00/88.75 which was higher than the standard gain of 80/80, and the students’ achievement after instruction by the practical package showed improvement in their reading skills at a higher rate than before instruction at a statistically significant level of .05.